Le corps platonicien, preuve et épreuve de la transcendance - Frédéric Fauquier (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
What is the place of the body in a dualistic system which organizes principles into hierarchy? Principles can be arranged into three postures: Platonist, Gnostic and Christian. In the Platonist posture, the body is, ambiguously, both a touchstone and a proof of transcendence. On the one hand, it bars access to the intelligible through its darkness and dispersion; on the other hand, it reveals the intelligible through its form.